The Role of the Dikyasa Unit in Community Education to Reduce Traffic Violations in the Barelang Police Legal Area - Raynaldo Sembiring (Advances in Police Science Research Journal, 2021)
This research was motivated by the increase in traffic violations committed by the community at the Barelang Police. The National Police in this case has the responsibility to reduce and prevent these problems. Preemptive measures are preventive measures that can be undertaken by the empowered unit to prevent and reduce traffic violations. Efforts to prevent this were carried out by the Unit at the Traffic Police of the Barelang Police through direct community service activities. So a research was carried out on the implementation of the Dikmas then by the dikyasa unit and the factors that influenced the unit personnel. This research was conducted with a qualitative approach, using descriptive research methods, as well as data collection techniques by interview and document study. The results of research on the implementation of community education are then analyzed through management theory which can see the stages of planning, organizing, implementing and controlling. Meanwhile, the influencing factors are analyzed using role theory which supports and hinders the implementation of direct education services. Then to optimize the communication theory because there are ways to change people's behavior, this is in line with the task of the unit dikyasa to change the community to be more obedient to traffic regulations. Based on the research results, it is suggested that the capacity of the unit personnel be improved through vocational education or improvement of personnel competence so that the personnel have good social communication to the community as well as the provision of rewards andactions and more attention to members. in order to increase the work motivation of the personnel. Conducting alternative education services to schools online due to this pandemic period so that community service to students can still be done and prepare interesting and systematic material to make it more interesting and easier to understand so as to prevent traffic violations by students.